Sustainability Report Sebagai Dasar Pengambilan Keputusan Investasi: Multiple Case Study - Angga Sudiartama, I Wayan; Sudana, I Putu; Budiasih, I Gusti Ayu Nyoman; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2022)
This study aims to identify and analyze using a Multiple Case Study on the use of information in the Sustainability Report by investors on the Indonesia Stock Exchange. Types of data, namely opinions, attitudes, experiences, or characteristics of the informants. Informants were determined by Snow Balling sampling. Data were collected through in-depth interviews. The analysis technique is in the form of data reduction, data display, and drawing conclusions. The technique of checking the validity of the data used in this study is a qualitative validity technique. The results show that the information in the Sustainability Report presents company information from various aspects. Starting from internal activities to external activities carried out by the company for social and environmental interests. Investor behavior always considers information related to the company for decision-making analysis. Each investor has their own strategy and has its own portion of the use of information in the Sustainability Report. Keywords:  Sustainability Report; Investment Decision; Investor; Multiple Case Study.